Diversidade genética do programa de melhoramento do guaranazeiro (Paullinia Cupana var. sorbilis ( Mart.) Ducke), utilizando marcadores Trap e Srap - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The guarana (Paullinia cupana var. Sorbilis (Mart.) Ducke) is a native species from the Amazon region rich in natural caffeine. Embrapa Western Amazon develops guarana breeding program based on clonal selection and recurrent selection to obtain cultivars and progenies with desirable agronomic characteristics. The use of molecular markers has been successfully applied in breeding programs to monitor genetic diversity and assist in marker-assisted selection. Thus, the present study aims to evaluate the genetic diversity of guarana improvement program, using TRAP (Target Region Amplification Polymorphism) and the SRAP (Sequence-Related Amplification Polymorphism). The work was divided into two parts: the first to test the potential of TRAP and SRAP markers, using subsamples of 60 BAG (Active Germplasm Bank) and the second to analyze the genetic diversity six progenies of half brothers guarana. In the BAG a polymorphism observed percentage of 79% (TRAP) and 74.5% (SRAP). The Dice coefficient ranged from 0.64 to 0.87, forming four groups in the dendrogram, where one concentrated 82% of the studied material. In the progenies of half brothers, polymorphism percentage was 85% for the TRAP and 76% for SRAP. The genetic diversity of Nei (H) was 0.20 and the Shannon index (I) of 0.30. The AMOVA showed that the highest percentage of variation is within the progenies (54%). With these results, the TRAP and SRAP markers showed potential genetic diversity studies in guarana breeding program.
Keywords: Germoplasma; Progênies; Espécies amazônica; Poliplóides; Amazon species; Germplasm; Progeny; Polyploid; CIÊNCIAS BIOLÓGICAS: GENÉTICA: GENÉTICA VEGETAL